Linear A versus Linear B administrative systems in the sphere of religious matters - Tomas, Helena (2010)
The majority of Linear A texts is divided into two groups, administrative and votive. Only the former exists in Linear B, although issues related to religion appear on its administrative documents. Substantial understanding of Linear A administrative texts has been achieved through comparisons to similarly organised Linear B texts, principally clay tablets, but this has not yet resulted in identifying religious issues on Linear A tablets. By pointing out significant differences between Linear A and Linear B administrative systems in terms of types of documents, pinacology and epigraphy, the intention of this paper is to stress the risk of over-reliance on Linear B records in attempting to interpret those in undeciphered Linear A. The fact that religious matters were recorded on Linear B administrative texts does not necessarily mean that the same was done on Linear A documents. This may represent another major difference between the two systems, hence the title of the paper.
Projekt MZOS
ENG